PENGARUH METODE CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR MATERI PECAHAN DAN DESIMAL PADA SISWA KELAS V - Zamri, Nur Aini; Utami, Widya; Sihombing, Sartika Putri Ruth Angel; Maranata, Sela (Universitas Negeri Medan, 2025)
The purpose of this study was to evaluate the effect of the Contextual Teaching and Learning (CTL) method on students’ mathematics learning outcomes in fractions and decimals among fifth-grade students at SD Muhammadiyah 18 Medan. This study employed a quantitative approach with a pre-experimental one-group pretest–posttest design involving 22 students. Data were collected through achievement tests and analyzed using a paired-sample t-test. The results indicated an improvement in students’ average scores from 56.09 on the pretest to 65.82 on the posttest, accompanied by an increase in the proportion of students in the Very Good category and a decrease in the Poor category. Therefore, the CTL method has a positive and significant effect on improving students’ mathematics learning outcomes.